Adjusting the digital library wind to reach right destination – Sri Lankan prospective - Arulanantham, S. (International Conference on Digital Libraries (ICDL), 2013)
[Current era emphasizes increased reforms of different initiatives in the field of digital libraries. Impacts of these reforms on Sri Lanka have made an attention on the necessity of thinking according to the current trend. The purpose of this research is to s explore the milestones in digital library tradition at Sri Lankan level, and to suggest proper directions of digital Library environment in Sri Lanka. Descriptive method with comparative analysis is used in this study to analyze and identify the right direction and new bench marking practices of digital libraries in Sri Lankan perspective. Findings of this study suggests that need of policy decision at National level to bond the collective effort on digital library, moving from isolated digital collections to interoperable digital libraries, and maintaining the international standards of digital library development are appropriate pathways for the effective digital library environment in Sri Lanka.]
Keywords: Digital libraries; Electronic libraries; Sri Lanka; Information policy; Library services